Ὁ μάγιστρος Θεόκτιστος καί ὁ Θεόδωρος Στουδίτης. Μοναστηριακός Βίος καί Πολιτική - ΚΟΥΝΤΟΥΡΑ-ΓΑΛΑΚΗ Ελεωνόρα (Byzantina Symmeikta, 1998)
Eleonora Kountoura-Galaki The magister Theoktistos and Theodore the Studite: Monastic Life and Policy. The quaestor Theoktistos was among the leading officials who took part in the conspiracy of the logothete Nicephorus against the empress Irene (802). He was identical with the magister Theoktistos who, as a supreme member of the Senate, received in 808 the letter No. 24 by Theodore the Studite. With this letter Theodore hoped that he could persuade magister Theoktistos to intervene to the emperor Nicephorus I, in order to avoid banishment. The magister, however, did not play a prominent role under the reign of Nicephorus and Theodore was forced to abandon the City. During the brief reign of Michael I, where we can observe the weakening of the imperial institution and the simultaneous uprise of the senatorial power as well as the rise of the fanatic monks (the monastery of Studion experienced a significant prosperity at that time) magister Theoktistos and Theodore the Studite had then powerfully participated in political life and had played a crucial role in it. Probably the same Theoktistos received one more letter (No 123) by Theodore the Studite after the accession of Leo V.